2017
DOI: 10.1098/rsbl.2016.0874
|View full text |Cite
|
Sign up to set email alerts
|

Artificial night lighting inhibits feeding in moths

Abstract: One major, yet poorly studied, change in the environment is nocturnal light pollution, which strongly alters habitats of nocturnally active species. Artificial night lighting is often considered as driving force behind rapid moth population declines in severely illuminated countries. To understand these declines, the question remains whether artificial light causes only increased mortality or also sublethal effects. We show that moths subjected to artificial night lighting spend less time feeding than moths in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
58
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 80 publications
(65 citation statements)
references
References 19 publications
6
58
0
1
Order By: Relevance
“…The negative population trends of moth species that are nocturnally active or have positive phototaxis agree with findings at the level of individuals, where moths show reduced foraging, pollen transport, dispersal and reproduction when subjected to artificial light compared to dark conditions (Altermatt et al., ; Macgregor et al., ; Van Geffen et al., ; Van Langevelde et al., ). In experiments on individual behaviour, the effects of lamps that differ in spectral composition can be tested (e.g.…”
Section: Discussionsupporting
confidence: 76%
“…The negative population trends of moth species that are nocturnally active or have positive phototaxis agree with findings at the level of individuals, where moths show reduced foraging, pollen transport, dispersal and reproduction when subjected to artificial light compared to dark conditions (Altermatt et al., ; Macgregor et al., ; Van Geffen et al., ; Van Langevelde et al., ). In experiments on individual behaviour, the effects of lamps that differ in spectral composition can be tested (e.g.…”
Section: Discussionsupporting
confidence: 76%
“…Possibly, these effects could be the result of changes in duration of feeding by moths under different lamp types; moths spend less time feeding under artificial light than in darkness, and the effect is strongest for lighting containing a high proportion of short wavelengths (van Langevelde et al. ), such as many commercially available LEDs, including those used in our study (Fig. ).…”
Section: Discussionmentioning
confidence: 90%
“…Their interactions with flowers can be directly affected through reduced feeding (van Langevelde et al. ), and we have previously found that pollen transport by nocturnal moths can be disrupted by the presence of full‐night (FN) lighting by HPS street lights (Macgregor et al. ): Moths at lit sites were attracted upwards to street lights, reducing the time they spent at the level of the field margin, where interactions with flowers might take place, compared to unlit sites.…”
Section: Introductionmentioning
confidence: 99%
“…Artificial light at night affects insects in more ways than mere attraction. It has been shown to interfere with pollination (Macgregor et al., ), feeding (van Langevelde et al., ), chemical communication (van Geffen et al., ), mating behavior (van Geffen et al., ), and disrupt initiation of diapause (van Geffen et al., ). It is currently unknown to what extent the model presented here is applicable for other impacts of artificial light on insects, besides attraction.…”
Section: Discussionmentioning
confidence: 99%